Evaluating the influence of direct marketing on company performance in the bakery and confectionery Industry: a case of Bakers Inn, Gweru - Mangweni, Innocent (Midlands State University, 2017)
With the growing level of competition in the Bakery and Confectionery Industry it is important for a company to maintain and grow its market share to gain an edge over competitors. This research aimed at evaluating the influence of direct marketing on company performance in the Bakery Sector. Companies gain competitive advantage through a more targeted marketing strategy. The major focus of this research was to establish the areas where various authorities agree or disagree then fill in the existing gaps. Different direct marketing channels were considered and different stakeholders gave their views on the practice of direct marketing. The researcher highlighted the brief background of the marketing communication concept and direct marketing concept as communication is important for organizations to create brand awareness and promoting the brand. Bakers Inn management and customers provided data to achieve the objectives of this study. Stratified random sampling was a probability sampling technique used on this research. The researcher also obtained data from secondary data sources some of which are out dated thus making it difficult for the researcher to obtain current information. Explorative and descriptive research designs were used as well as a sample of 104 to obtain more data relating to the success of this study. Bakers Inn employees were interviewed while the customers were given questionnaires to fill. Quantitative findings were presented and analyzed using pie charts, graphs and tables while qualitative results were presented in paragraph sequences. The findings revealed that direct marketing has a positive influence on the company performance. It is accountable for building customer relationships and help companies improve their return on investment it allows for a more targeted marketing approach through personalization and customization of marketing efforts. The research recommends Bakers Inn to actively capture consumer’s details to update its database and use mobile phone promotions to solicit for more loyal customers. Additionally it is also recommended that Bakers Inn should adopt direct marketing as marketing and strategic tool for gaining competitive edge and to ensure market share and sales revenue growth.